2010
DOI: 10.1111/j.1477-2574.2009.00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-fetoprotein and tumour size are associated with microvascular invasion in explanted livers of patients undergoing transplantation with hepatocellular carcinoma

Abstract: MVI greatly increases the risk of recurrence and death after LT for HCC, and is strongly associated with tumour size and AFP > 100.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 26 publications
4
84
2
Order By: Relevance
“…However, it seems difficult to use the cut-off value of 400 ng/mL to directly exclude patients from a waiting list, because this value has been mostly studied as part of algorithms that include tumor volume, tumor size, the MC, and/or the UCSFcriteria. Moreover, many other cutoff values have been suggested, such as 100 ng/mL [47,57,67] and 200 ng/ mL [10,68] . The level of evidence to define an optimal value is very weak and thus calls for further studies.…”
Section: Defining a Cut-off Value For Afpmentioning
confidence: 99%
“…However, it seems difficult to use the cut-off value of 400 ng/mL to directly exclude patients from a waiting list, because this value has been mostly studied as part of algorithms that include tumor volume, tumor size, the MC, and/or the UCSFcriteria. Moreover, many other cutoff values have been suggested, such as 100 ng/mL [47,57,67] and 200 ng/ mL [10,68] . The level of evidence to define an optimal value is very weak and thus calls for further studies.…”
Section: Defining a Cut-off Value For Afpmentioning
confidence: 99%
“…Preoperative AFP may be the best available surrogate marker for micro-vascular invasion and the biological aggressiveness of the tumour. Several studies have identified a high pre-operative AFP as a risk factor for recurrence and reduced survival [18,[20][21][22] . We have shown AFP predicted reduced disease free survival, independent of both tumour size and micro-vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…A United States study including 101 patients showed that AFP > 100 ng/mL (OR = 5.0, P = 0.006) and tumor size (OR = 4.1, P = 0.013) were correlated with microvascular invasion and post-LT recurrence [12] . Another Polish study including 121 HCC patients confirmed the validity of 100 ng/mL as cut-off value in predicting the risk of post-LT recurrence in patients meeting San Francisco criteria or up-to-seven criteria [13] .…”
Section: Recurrence: Role Of Static Valuesmentioning
confidence: 99%
“…The San Francisco transplant center underlined the recent implementation in their inclusion policy for LT to include patients with AFP levels > 1000 ng/mL only if LRT enabled to decrease this level beneath 500 ng/mL [21] . A Canadian study including 48 patients showed by 1901 July 28, 2015|Volume 7|Issue 15| WJH|www.wjgnet.com McHugh et al [12] 2010 101 United States 100 Grąt et al [13] 2014 121 Poland 100 Abdel-Wahab et al [14] 2013 170 (LDLT) Egypt 200 Lai et al [15] 2011 153 Italy 210 Harimoto et al [16] 2013 167 (LDLT) Japan 300 Merani et al [6] 2011 6817 United States 400 Toso et al [7] 2009 6478 United States 400 Zheng et al [8] 2008…”
Section: From Static To Dynamicmentioning
confidence: 99%